Usaha Bisnis E-commearce Perspektif Ekonomi Islam (studi pada bisnis @lisdasasirangan) - Lisda Aisyah; Siti Achiria (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2019)
E-commerce is a transaction which is referred to as an online transaction where this transaction uses cyberspace as a place to transact. A business that uses in the present era is not only modeled with the seller and the buyer makes a face-to-face transaction but can be done with an online business or called an e-commerce business.               The purpose of this study is to find out how the business e-commearce business perspective of Islamic economics. This study is a field research (qualitative research) that is qualitative descriptive and library library. The research subject is the owner of a business business @lisdasasirangan and the object of research is the application of a business venture e-commearce perspective of the market structure of Islamic economics. Data collection techniques with interviews are then processed with editing techniques, categorization and interpretation, then analyzed descriptively qualitatively to draw conclusions.               Based on research on business ventures e-commearce perspective of the market structure of Islamic economics. The e-commerce business is a market in the modern era that explores the global market. The e-commerce business will continue to grow along with the development of technology, technological developments not only develop in education but also in the economic field, namely in the field of market structure. The end of an e-commerce business can be compared to the online market. But in this type of online market, there are many sellers and buyers with various kinds of goods sold and offered so that this online market can be called a perfectly competitive market.